Persepsi Siswa SMA Fides Kefamenanu terhadap Pelatihan Ekstrakurikuler Jurnalistik - Meylisa Yuliastuti Sahan; Imanuel Kamlasi; Anselmus Sahan; Maria Wihelmina Wisrance (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2023)
Abstract The journalism training program which was launched through community service activities at SMAK FQI Kefamenanu in August 2022 aims to train them how to write news, find sources and publish it on the school bulletin. To find out their perceptions (N=27) about journalism and the training, at the end of the activity they were presented with a questionnaire containing 25 questions. The 25 questions relate to three main issues, namely their reasons for choosing journalistic activities, their understanding of journalism and the implementation of journalism extracurriculars. The results of the data analysis revealed that they had a positive perception (235 respons or 87%) of extracurricular journalistic activities at their school, understood the world of journalism (98 respons or 38% agreed) and agreed with extracurricular activities (103 respons or 38%) both at school and journalistic training conducted by the Unimor Service Team for them. Therefore, journalistic training should be made an important part of all extracurricular and curricular activities so that their interests, talents and abilities can really be developed properly. Keywords: perception, SMA Fides, training, journalism